The predictive value of the pre-PCI prognostic nutritional index combined with the geriatric nutritional risk index for one-year outcomes in patients with chronic total occlusion - Bin, Zhang; YuRong, Sun; Hangrui, Bai; JingSi, Zhang; Yi, Lu; FengYi, Liu; Qian, Yang; YangYou, Zhang; Bo, Luan; YanChun, Ding; XiaoJiao, Zhang (Frontiers in Nutrition, 2025)
AimChronic total occlusion (CTO) is associated with high rates of major adverse cardiovascular and cerebrovascular events (MACCEs) after percutaneous coronary intervention (PCI). Nutritional and inflammatory status are increasingly recognized as key prognostic factors. This study aimed to evaluate the predictive value of the prognostic nutritional index (PNI) combined with the geriatric nutritional risk index (GNRI) for MACCEs in CTO patients undergoing PCI.MethodsA total of 395 CTO patients from Northeast China who were treated with PCI at Liaoning Provincial People’s Hospital between February 2019 and December 2023 were retrospectively analyzed. Baseline clinical, laboratory, and procedural data were collected. The PNI and GNRI scores were calculated based on pre-PCI laboratory test results, and patients were followed for 12 months to monitor the occurrence of MACCEs. Independent predictors were identified using logistic regression analysis, and the predictive performance of three models was evaluated using ROC curves, C-statistics, net reclassification improvement (NRI), integrated discrimination improvement (IDI), and Kaplan–Meier survival analysis.ResultsDuring follow-up, 125 patients (31.6%) experienced MACCEs. Both PNI-GNRI were independent predictors of MACCEs risk. Adding PNI to the baseline risk model increased the C-statistic from 0.696 to 0.770 (p < 0.001). Incorporating GNRI further increased it to 0.826 (p < 0.001), with significant improvements in NRI (0.308) and IDI (0.207). Kaplan–Meier analysis demonstrated that patients with low PNI or GNRI scores had significantly higher cumulative incidence of MACCEs. Subgroup analyses confirmed the stability of these associations across various patient strata.ConclusionBoth PNI-GNRI are independent predictors of MACCEs, and their combined model provides superior prognostic stratification for CTO patients compared with traditional risk models, particularly in elderly patients. Comprehensive assessment of nutritional and inflammatory status enables precise perioperative risk stratification. It also offers guidance for individualized management, nutritional interventions, and long-term rehabilitation.